Exploratory and collaborative learning experience in immersive environments: Implementation and findings from an archaeological domain - Gütl, C.; Tomes, L.; Pirker, J.; Chang, Vanessa (2016)
© Springer International Publishing Switzerland 2016.This paper describes a multi-user learning environment in a virtual world setting. An exploratory and collaborative learning using an educational scavenger hunt metaphor form the basis for student learning and engagement in virtual world. The learning experience is based on the following elements: exploration – students explore the learning content on their own, and build a knowledge base. Cooperation and Collaboration – students cooperate and collaborate to uncover information, share findings, and gain knowledge and skills. Discussion and Reflection – students discuss and solve problems together, and exercise reflective learning. Based on this idea, three main contributions are provided in this paper: Firstly, a pedagogical model which combines immersive, online, and virtual collaboration with an exploratory teaching approach. Secondly, the learning tasks and interactions are incorporated by a flexible to use set of tools in the virtual world Open Wonderland. Finally, an experimentation study evaluating the virtual world in the learning domain Egyptology.